A molecular electron density theory study of the [3 + 2] cycloaddition reaction between an azomethine imine and electron deficient ethylenes. (27th February 2018) - Ríos‐Gutiérrez, Mar; Nasri, Lilia; Khorief Nacereddine, Abdelmalek; Djerourou, Abdelhafid; Domingo, Luis R.
Abstract: The selectivity and the nature of the molecular mechanism of the [3 + 2] cycloaddition (32CA) reaction of an azomethine imine (AI 12) with p ‐nitrobenzylidenemalononitrile (NBMN, 13) have been theoretically studied within the Molecular Electron Density Theory using DFT methods at the MPWB1K/6‐31G(d) computational level. Analysis of the Conceptual DFT reactivity indices indicates that the strong nucleophilic character of AI 12 together with the high electrophilic character of NBMN 13 accounts for the strong polar character of this 32CA reaction, which demands very low activation energy. Analysis of the energy profiles indicates that this polar zw‐type 32CA reaction proceeds completely with a meta / exo selective pathway, in great agreement with the experimental data. Analyses of both molecular electrostatic potential and the non‐covalent interactions at the meta regioisomeric TSs allow explaining the observed exo stereoselectivity. Electron Localisation Function topological analysis indicates that the studied 32CA reaction takes place via a non‐concerted two‐stage one‐step mechanism as a [2n + 2τ] process. Abstract : A computational study of the [3+2] cycloaddition reaction of an azomethine imine with electron deficient ethylene has been performed using the molecular electron density theory. This 32CA reaction is characterized by full meta/exo selectivity and proceeds via a nonconcerted two‐stage one‐step mechanism as a [2n+2τ] process with a high polarity.